COMMUNICATION STRATEGIES USED BY ALFRED THE GREAT AND UHTRED OF BEBBANBURG IN “THE LAST KINGDOM” SERIES ON NETFLIX - Ahyar, Muhammad; Mustikawati, Yunitari (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
The research is entitled “Communication Strategy Used By Alfred And Uhtred Of Bebbanburg in “The Last Kingdom” Series On Neflix” This study aims to analyze the use of two main characters Alfred and Uhtred in “The Last Kingdom” by Stephen Butchard (2015) by using Durnyei and Scott`s theory (1997) and Scott and his colleagues theory (1998). Direct communication, indirect communication, and interactional communication modification device strategies by Durnyei and Scott (1997) and message-level of communication strategy, interactional strategy, and negotiation communication strategy by Scott and his colleagues (1998) are used to analyze the communication strategy both Alfred and Uhtred used in the series “The last Kingdom”. Descriptive qualitative research is used in this study, data obtained from the text of dialogs of Alfred and Uhtred interaction with other characters or Alfred and Uhtred`s interaction that contain elements of communication strategy. The result of the research show that there are 49 communication strategies implemented between the two characters according the theories being used. The research data were obtained from the extractions of communication strategy used by Alfred and Uhtred. The findings provided a deep insight into how “Alfred” and “Uhtred” use of communication strategies in various ways such as direct message, indirect command, message-level, interactional and negotiation can be useful in many kinds of communication especially as a leader, chairmen or chairperson. This research is expected to contribute to the understanding of literatures and how the reflected of communication strategy of Alfred and Uhtred in the movie literary works.